Application of the Preparation of Closed-End Company Shareholders' Meeting Minutes Through Electronic Means by a Notary - Gusti Ramadhan; Thea Farina; Ariani Yestati; Mulida Hayati (Green Publisher Indonesia, 2026)
Digital transformation in the Society 5.0 era encourages the use of information technology in various aspects of life, including in notarial practice and the holding of General Meetings of Shareholders (GMS). Law Number 40 of 2007 concerning Limited Liability Companies through Article 77 has provided the legal basis for holding GMS through electronic media. However, detailed technical regulations are currently only available for Public Companies, thus creating a normative vacuum in the implementation of electronic GMS in Private Limited Companies, particularly regarding the preparation of deed releases by notaries. This study aims to analyze the implementation of the preparation of deed releases for Public Limited Companies GMS through electronic media by notaries and identify the normative, technical, and sociological obstacles that influence its implementation. This study uses an empirical juridical approach with participatory observation methods and semi-structured interviews with notaries in Palangka Raya City. The results show that the absence of technical regulations causes notaries to apply the principle of excessive caution, which has an impact on the stagnation of innovation in notarial practices. The main obstacles include the lack of implementing regulations, limited technological infrastructure, and low trust and understanding of business actors regarding the electronic GMS mechanism. This research emphasizes the need for regulatory updates that explicitly regulate the implementation of electronic GMS for closed PTs and standards for the preparation of deed releases by notaries to ensure legal certainty and the adaptation of notarial practices to developments in information technology.